THE EFFECT OF WEIGHT TRAINING USING (KETTLEBELLS) ON THE DEVELOPMENT OF MUSCULAR STRENGTH OF THE ARMS AND JUMP SHOOT IN BASKETBALL - Dr. Manaf Hameed Majeed; M.Sc. Ahmed Subhi Shakur (Galaxy International Interdisciplinary Research Journal, 2023)
Sports training is one of the sciences that keep pace with the development in the sports field, especially that sports training is the science specialized in keeping pace with developments in the sports field in terms of theories and methods of training as well as tools that contribute significantly to the development of the physical, motor and functional abilities of players. The use of (kettlebells) is one of the tools for training muscular strength, which allows free and unrestricted movement of the wrist and arms, and the researchers have considered that using this tool will help in developing the element of strength for the arms, which will help in developing shooting from jumping in basketball.